2004
DOI: 10.1373/clinchem.2004.032656
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural C-Reactive Protein Is Not Associated with Angiographic Restenosis or Target Lesion Revascularization after Coronary Artery Stent Placement

Abstract: Background:We assessed the predictive value of preprocedural plasma C-reactive protein (CRP) concentrations and statin therapy on 6 months angiographic and 1-year clinical outcome after nonurgent coronary stent placement. Methods and Results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
4
19
0
2
Order By: Relevance
“…We previously showed that stent placement in humans is followed by abundant cellular infiltration around the metal stent struts (22 ), indicating a local inflammatory response. Our present results on systemic indicators of inflammation were all negative, although they were in accordance with our previous negative results for C-reactive protein as a prognostic marker for angiographic ISR (23 ). To our knowledge, our study is the first attempt to associate individual differences in cytokine production with angiographic outcome in a large cohort of patients, all treated electively with the same coronary stents.…”
Section: Discussionsupporting
confidence: 92%
“…We previously showed that stent placement in humans is followed by abundant cellular infiltration around the metal stent struts (22 ), indicating a local inflammatory response. Our present results on systemic indicators of inflammation were all negative, although they were in accordance with our previous negative results for C-reactive protein as a prognostic marker for angiographic ISR (23 ). To our knowledge, our study is the first attempt to associate individual differences in cytokine production with angiographic outcome in a large cohort of patients, all treated electively with the same coronary stents.…”
Section: Discussionsupporting
confidence: 92%
“…The specific prognostic role of CRP in predicting restenosis in patients with acute coronary syndromes, who supposedly have more inflamed and unstable plaques and arteries, was not assessed in this study. However, the same group has recently published a large study confirming the predictive role of CRP on the risk of death and myocardial infarction after PCI (22 ), and their current study (4 ), notwithstanding the low-risk population and relatively small number of patients, has shown a trend in this direction. Because the data in favor of the predictive role of CRP for death and myocardial infarction are very consistent, patients undergoing PCI should not be denied a CRP measurement.…”
supporting
confidence: 56%
“…Indeed, the low risk was confirmed by the low rate of death or myocardial infarction 12 months after stenting, which was only 1.7% in the overall cohort. Moreover, the statistical power of this patient cohort to recognize predictive variables for restenosis may have been suboptimal, as evidenced by the surprising fact that a well-recognized and independent predictor of restenosis, such as diabetes mellitus (5 ), was not associated with either restenosis or target lesion revascularization in this study (4 ).…”
mentioning
confidence: 79%
“…These results were consistent with previous studies reporting the lack of an association between CRP and repeat revascularization after bare metal stent treatment. 34,35 …”
Section: Discussionmentioning
confidence: 99%